Does Quality Matter in Labour Input? The Changing Pattern of Labour Composition in New Zealand - Kam Leong Szeto; Simon McLoughlin (New Zealand Government, The Treasury, 2008)
The composition of the New Zealand workforce has changed considerably over the past two decades. Qualification levels have risen, labour force participation has trended upwards for women, immigrants have increasingly been sourced from Asia, and the large baby-boom cohort has contributed to an ageing of the workforce. The question is whether such compositional changes have affected the quality of labour. Our estimates show a large rise in labour quality since 1988 as a result of increasing qualification levels, particularly at university degree level. With age as a proxy for work experience, an ageing of the workforce also contributed to rising labour quality. The annual rise in labour quality averaged 0.6% from 1988 to 2005, which was comparable to the experience of Australia, the United States and the euro area. Although labour quality rose in every year of our sample period, the rise was not constant over time. The increase was much stronger in the first half of the period (1988 to 1997) than in the second half (1997 to 2005). By drawing a large number of lower-skilled people into work, the strength of recent employment growth may have dampened growth in labour quality. Accounting for changes in labour quality has implications for labour productivity. Almost half of labour productivity growth of 1.4% per annum since 1988 can be attributed to the rise in labour quality. Labour productivity measured as output per quality-adjusted working hour rose by 0.8% per annum on average from 1988 to 2005, with annual growth of 0.5% in the first half of the period and 1.1% in the second half.
Keywords: J21; J24; J31; J61; 330; Labour Quality; Human Capital; Wage Differentials; Labour Productivity; Arbeitsproduktivität; Humankapital; Lohnstruktur; Neuseeland